Status of the JET ITER-Like Antenna High-Power Prototype Test Program - Goulding, R.H.; Baity, F.W.; Fadnek, A.; Freudenberg, K.D.; Nelson, B.E.; Rasmussen, D.A.; Sparks, D.O.; Durodie, F.; Hosea, J.C.; Loesser, G.D.; Nightingale, M.; Walton, R. (AIP conference proceedings, 2005)
Previous tests of a High Power Prototype (HPP) comprising one quadrant of the JET ITER-Like ICRF Antenna have indicated the need for some design modifications in order to achieve 10 s pulses coupling the full design power (7.1 MW) into the reference plasma load (R' = 4 {omega}/m). These modifications have now been made to the HPP, as well as to the design of the ITER-Like Antenna itself. In particular, maximum current densities have been reduced or otherwise accommodated in key areas. New current straps for the HPP have been fabricated from stereo-lithography-based investment castings. Design modifications to the antenna enclosure have also been implemented. This work has been materially assisted through the use of CST Microwave Studio (MWS), a commercially available 3-D electromagnetic modeling package. Essentially the full engineering CAD model of the HPP current straps and antenna enclosure has been ex-ported from ProE to MWS. Computed current density profiles have been introduced into an ANSYS thermal model. These activities will be discussed, as well as the current status of the HPP test program.